The abundance and distribution patterns of sea urchins in Botubarani waters, Tomini Bay, Indonesia - Wiyanti Abd Kadir; Sri Nuryatin Hamzah; La Nane (Gorontalo State University, 2021)
This study aims to determine the abundance and distribution patterns of sea urchins in Botubarani Waters, Kabila Bone District, Bone Bolango Regency. This research was conducted from July to August 2020. A total of three research stations were established, namely West Tamboa, Central Tamboa and East Tamboa. The abundance of sea urchins was calculated using a quadrant transect measuring 1 × 1 m, which was laid 25 m perpendicular to the coastline using a line transect. Sea urchin species found were identified in situ and the distribution pattern of sea urchins was calculated using the morista dispersion index. The results showed that there were 5 types of sea urchins in Botubarani Beach, namely Echinometra mathaei, Diadema setosum, Echinotrix calamaris, Echinotrix diadema and Tripneustes gratilla. The sea urchin type Echinometra mathaei is the species with the highest abundance in all research stations, namely 25 ind./m2 at Tamboa Barat station, 9 ind./m2 at Tamboa Tengah station and 7 ind./m2 at Tamboa Timur station. The distribution patterns of sea urchins found in Botubarani waters include clusters for Echinometra mathaei and uniform patterns for sea urchins Diadema setosum, Echinotrix calamaris, Echinotrix diadema and Tripneustes gratilla. ANOVA analysis results show that there is no significant difference between sea urchin abundance and water quality parameters in all research stations. This indicates that there is no difference in environmental conditions at the three sampling locations.